Ascites associated with a raised CA125 level - G. Silva, Filipe (2000)
The authors presenta case of a 48 year-old woman admitted for fever, sweating, chills, weight Joss and ascites, having had the diagnosis of peritoneal tuberculosis made histologically from a peritoneal biopsy. The patient had an elevated CA 125. With the antibacillary treatment, the patient became asymptomatic and the CA 125 value returned to normal. The authors make a brief discussion about the characteristic of this form of tuberculosis.